2015
DOI: 10.1371/journal.pone.0124410
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-302a Suppresses Tumor Cell Proliferation by Inhibiting AKT in Prostate Cancer

Abstract: Micro (mi) RNAs are important regulators involved in various physical and pathological processes, including cancer. The miRNA-302 family has been documented as playing a critical role in carcinogenesis. In this study, we investigated the role of miRNA-302a in prostate cancer (PCa). MiRNA-302a expression was detected in 44 PCa tissues and 10 normal prostate tissues, and their clinicopathological significance was analyzed. Cell proliferation and cell cycle analysis were performed on PCa cells that stably express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 22 publications
2
43
1
1
Order By: Relevance
“…In addition, upregulation of the miR‐302/367 cluster in PCa has protumorigenic effects in vivo and in vitro through enhanced cell proliferation, sphere formation, and migration through the miR‐302/367/LATS2/YAP pathway . However, in another PCa study, miR‐302a functioned as a tumor suppressor by influencing the AKT‐GSK‐3β‐CCND1 and AKT‐p27Kip1 pathways . The second PCa study did not verify the conclusions in animal models, and the clinical sample size was not large enough.…”
Section: Functions and Mechanisms Of Mir‐302 Cluster In Tumor Developmentioning
confidence: 94%
“…In addition, upregulation of the miR‐302/367 cluster in PCa has protumorigenic effects in vivo and in vitro through enhanced cell proliferation, sphere formation, and migration through the miR‐302/367/LATS2/YAP pathway . However, in another PCa study, miR‐302a functioned as a tumor suppressor by influencing the AKT‐GSK‐3β‐CCND1 and AKT‐p27Kip1 pathways . The second PCa study did not verify the conclusions in animal models, and the clinical sample size was not large enough.…”
Section: Functions and Mechanisms Of Mir‐302 Cluster In Tumor Developmentioning
confidence: 94%
“…Furthermore, miRNA-302a inhibits AKT expression through a binding with its 3 0 untranslated region, and alterations of the AKT/GSK3b-cyclin D1 and AKT-p27Kip1 pathway. These results reveal miRNA-302a as a tumor suppressor in PCa, and that it may be useful in a new therapeutic strategy in PCa [131]. Other important markers which could be potential therapeutic targets in PCa are a group of 12 miRNAs that bind the 3c-untranslated region of Bmi-1 mRNA in PC-3 cells.…”
Section: Mirnas As Therapeutic Tool In Prostate Cancermentioning
confidence: 74%
“…Furthermore, total Akt and ERK1/2 expression levels were also determined by western blot analysis in TE-10 and ECA109 cells, and overexpression of miR302a did not markedly differ between groups. miR302a overexpression has been demonstrated to significantly inhibit cell proliferation by inhibiting Akt in colon cancer and prostate cancer (10,27). Furthermore, miR-302 has also been reported to inhibit cancer cell proliferation via the Akt signaling pathway, and the microRNA-302-367 cluster suppressed the proliferation of cervical carcinoma cells through the novel target Akt1 (28).…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al (9) demonstrated that miR302a is involved in the inhibition of ovarian cancer cell proliferation, and enhances cell apoptosis through targeting syndecan 1. In addition, miR302a suppresses tumor cell proliferation by inhibiting protein kinase B (AKT) in prostate cancer (10). However, miR302a expression and its involvement in esophageal cancer remain undetermined, and the underlying mechanisms of miR302a in esophageal cancer cells remain unknown.…”
Section: Introductionmentioning
confidence: 99%